MSME Batik Tulis Banyuripan in Klaten Recovering from COVID-19 through Repositioning Strategies - Pujiastuti, Eny Endah; Utomo, Humam Santoso; Haryono, Sigit (RSF Conference Series: Business, Management and Social Sciences, 2021)
The covid-19 pandemic has been running for almost 2 (two) years and has had such a great impact on MSMEs. Batik Tulis Banyuripan was also affected and experienced a management crisis. In order to mitigate the risk, it is necessary to take immediate measures for recovery. The purpose of this study is to investigate how Marketing Recovery Strategies, through appropriate repositioning strategies, are able to increase sales and restore the batik business. The sample was the Banyuripan Batik Write Association in Central Java, Indonesia, which consists of batik producers typically of Klaten, Central Java. Data were collected using in-depth interviews and focus group discussions for data analysis technique using Triangulation. The results showed that the UMKM Batik Tulis Banyuripan performs recovery steps utilizing a marketing recovery strategy approach. The first step is a market analysis where the repositioning strategy is the result of the alignment of the changing needs of the external market and the internal capacity to respond to them. Secondly, Batik SMEs also carry out external and in-house environmental analyses. By analyzing both the external and internal environment, it will help Batik Tulis MSMEs better understand the market. Third, the Banyuripan Batik Tulis MSMEs are repositioning (repositioning strategies). The written batik also conducts an analysis of the external and internal environment that helps Batik Tulis MSMEs to better understand the market.